1983
DOI: 10.1152/ajpheart.1983.245.1.h22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changes in magnesium ion concentration on cat cerebral arterioles

Abstract: The effect of changes in cerebrospinal fluid (CSF) concentration of magnesium ion ([Mg2+]) on pial arterioles was investigated in anesthetized cats equipped with acutely implanted cranial windows for the observation of the pial microcirculation. Increased [Mg2+] caused vasodilation, whereas decreased [Mg2+] caused vasoconstriction. The effect of [Mg2+] was dose dependent and was the same in small and larger arterioles. There was an interaction between CSF [Mg2+] and calcium ion concentration ([Ca2+]), such tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
0
19
0
3
Order By: Relevance
“…19) Our preclinical study demonstrated that intra-cisternal infusion of 10 mmol/l magnesium sulfate solution improved the CBF reduced by experimental SAH in the rat. 13,21) The optimal concentration may be 10 mmol/l magnesium sulfate solution. The vasodilatory effect of magnesium infusion therapy may depend on maintaining the CSF Mg 2+ concentration at 3 mEq/l more than the concentration of the infusate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19) Our preclinical study demonstrated that intra-cisternal infusion of 10 mmol/l magnesium sulfate solution improved the CBF reduced by experimental SAH in the rat. 13,21) The optimal concentration may be 10 mmol/l magnesium sulfate solution. The vasodilatory effect of magnesium infusion therapy may depend on maintaining the CSF Mg 2+ concentration at 3 mEq/l more than the concentration of the infusate.…”
Section: Discussionmentioning
confidence: 99%
“…21) In contrast, in vitro studies clearly show that increased extracellular Mg 2+ concentration definitely causes vasodilation of both normal and contracted cerebral vessels in the presence of vasospasm-inducing agents. 11,17) Therefore, intra-cisternal administration of Mg 2+ is expected to reverse delayed cerebral vasospasm.…”
Section: Introductionmentioning
confidence: 97%
“…Vol. 11, No.6, 1991 pial arterioles in situ, magnesium causes a dose dependent vasodilatation that is probably due to a reduction in the influx of Ca 2 + into vascular smooth muscle cells (Seelig et al , 1983;Altura and Altura, 1984). Intravenously injected, magnesium induces dilatation of the basilar artery in cats after the ves sel has undergone spasm (Kapp et al , 1970).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, magnesium deficiency has been found to sensitize the vascular epithelium to prostanoids and induces rapid calcium-mediated vasospastic responses in cerebral blood vessels (91). Administration of magnesium decreases vascular resistance and causes vascular dilation (92). Furthermore, recent experimental data have demonstrated that magnesium sulfate injection reverses pressor effects and cerebral vasoconstriction previously induced by noradrenaline (93).…”
Section: The Role Of Magnesiummentioning
confidence: 99%